2011
DOI: 10.3945/jn.110.134270
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Epicatechin Promotes Survival of Obese Diabetic Mice and Drosophila melanogaster

Abstract: The lifespan of diabetic patients is 7-8 y shorter than that of the general population because of hyperglycemia-induced vascular complications and damage to other organs such as the liver and skeletal muscle. Here, we investigated the effects of epicatechin, one of the major flavonoids in cocoa, on health-promoting effects in obese diabetic (db/db) mice (0.25% in drinking water for 15 wk) and Drosophila melanogaster (0.01-8 mmol/L in diet). Dietary intake of epicatechin promoted survival in the diabetic mice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 39 publications
8
83
2
1
Order By: Relevance
“…Similarly, EC restored high TG, NEFA and T-Cho levels in high glucose-challenged HepG2 cells to control values. In line with these results, different cocoa extracts and EC reduced serum and hepatic lipid levels in diabetic rodents (Jalil, Ismail, Chong, Hamidc, & Syed Kamaruddina, 2009;Jalil, Ismail, Pei, Hamid, & Kamaruddin, 2008;Ruzaidi et al, 2005;Si et al, 2011), and grape procyanidins diminished lipid values in HepG2 cells (Guerrero et al, 2013). Moreover, it has also been reported that resveratrol and extracts rich in phenolic compounds from fruits and plants reversed the impaired lipid profile in the liver of diabetic rodents (Im et al, 2014;Kopec, Piatkowska, Leszczynska, & Koronowicz, 2013;Mokiran et al, 2014), as well as in lipidoverloaded hepatic cells .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similarly, EC restored high TG, NEFA and T-Cho levels in high glucose-challenged HepG2 cells to control values. In line with these results, different cocoa extracts and EC reduced serum and hepatic lipid levels in diabetic rodents (Jalil, Ismail, Chong, Hamidc, & Syed Kamaruddina, 2009;Jalil, Ismail, Pei, Hamid, & Kamaruddin, 2008;Ruzaidi et al, 2005;Si et al, 2011), and grape procyanidins diminished lipid values in HepG2 cells (Guerrero et al, 2013). Moreover, it has also been reported that resveratrol and extracts rich in phenolic compounds from fruits and plants reversed the impaired lipid profile in the liver of diabetic rodents (Im et al, 2014;Kopec, Piatkowska, Leszczynska, & Koronowicz, 2013;Mokiran et al, 2014), as well as in lipidoverloaded hepatic cells .…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, it has been reported that metabolites derived from a proanthocyanidin-rich extract of cocoa decreased lipid synthesis and excretion in HepG2 cells (Guerrero et al, 2013). Different studies have also demonstrated that cocoa or its main components, such as EC, exert hypoglycaemic and hypolipidaemic effects on several animal models of diabetes and insulin resistance (Cordero-Herrera, Martín, Goya, & Ramos, 2015a;Matsuia et al, 2005;Mokiran et al, 2014;Ramos et al, 2008;Ruzaidi, Amin, Nawalyah, Hamid, & Faizul, 2005;Si et al, 2011). Moreover, cocoa and dark chocolate have been reported to improve insulin sensitivity and lipid profile in healthy humans and T2D patients, alleviating the atherosclerotic cholesterol profile (Baba et al, 2007;Grassi et al, 2008;Mellor, Sathyapalan, Kilpatrick, Beckett, & Atkin, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…We found ten studies on flavonoids and lifespan studies in D. melanogaster. Three of them used single compounds such as the flavanol epicatechin and the flavonol fisetin (58)(59)(60) , the other seven studies were on cocoa powder, green tea extract, Ludwigia octovalvis extract, apple polyphenols, black tea extract (BTE) and BE (61)(62)(63)(64)(65)(66)(67) (Table 2).…”
Section: Flavonoids and The Lifespan Of Drosophila Melanogastermentioning
confidence: 99%
“…Epicatechin alone and in combination with exercise has an additive effect to stimulate myocardial angiogenesis (70). Obese, diabetic db/db mice have prolonged lifespan, along with a decrease in markers of inflammation and LDL-cholesterol when treated with epicatechin (79). It is important to note that these animal studies are observational in nature and need to be followed up by more mechanistic studies in the future.…”
Section: E682mentioning
confidence: 99%